2006
DOI: 10.1080/02652030500401181
|View full text |Cite
|
Sign up to set email alerts
|

Residues of DDT and HCH in wheat samples collected from different states of India and their dietary exposure: A multicentre study

Abstract: Under a multicentre study conducted by the Indian Council of Medical Research, 1712 samples of wheat grain/flour were collected from urban and rural areas in 11 states representing different geographical regions of India. These samples were analysed for residues of DDT (2,2-bis (p-chlorophenyl)-1,1,1-trichloro ethane) and different isomers of HCH (1,2,3,4,5,6-hexachloro cyclohexane, a mixture of isomers) by gas-liquid chromatography. Residues of DDT were detected in 59.4% of 1080 samples of wheat grain and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, it must stressed that cereal-based products and not wheat grains were studied in that work. Toteja et al (2006) reported much higher DDT concentrations in wheat harvested in India with a median of 13 μg kg −1 and a maximum of 7000 μg kg −1 in addition to the detectable quantities of HCH that were found. Łozowicka and Kaczyński (2009) reported generally low levels of DDT and its metabolites in agricultural crops harvested in Poland.…”
Section: Organochlorine Pesticidesmentioning
confidence: 91%
“…However, it must stressed that cereal-based products and not wheat grains were studied in that work. Toteja et al (2006) reported much higher DDT concentrations in wheat harvested in India with a median of 13 μg kg −1 and a maximum of 7000 μg kg −1 in addition to the detectable quantities of HCH that were found. Łozowicka and Kaczyński (2009) reported generally low levels of DDT and its metabolites in agricultural crops harvested in Poland.…”
Section: Organochlorine Pesticidesmentioning
confidence: 91%
“…A new multi-residue method for simultaneous determination of 405 pesticide residues in grain has also been developed (Guo-Fang et al 2006). Toteja et al (2006) determined residues of DDT and HCH pesticides in wheat grain and flour samples.…”
mentioning
confidence: 99%